Facility and microgrid location-allocation for integrated supply chain and transactive energy operations - Li, Honglin; Jin, Tongdan; Novoa, Clara (Applied mathematical modelling, 2023)
•Design low-carbon supply chain in manufacturing-renewables-climate nexus.•A first-of-its-kind of facility location-allocation model with transactive energy.•Strategically siting and sizing factories, warehouses and prosumer microgrids.•Allocating generation, energy trading, production, inventory and vehicle routing.•Synthesize product and energy markets under demand and supply uncertainty. Supply chain network design usually focuses on the uncertainties in materials, capacity, yield, and demand. However, the challenges of prosumer energy integration are not adequately addressed. This paper proposes an integrated facility and microgrid location-allocation model for achieving low-carbon supply chain operations at the nexus of manufacturing, renewables, and climate. The model strategically locates the site for establishing factories, warehouses, and microgrids subject to product demand and energy supply uncertainty. The model further allocates production, inventory, transportation, generation, and energy transactions to lower the net supply chain cost. The study represents a first-of-its-kind in jointly siting and sizing industrial facilities and prosumer microgrids under a unified optimization framework. The proposed model is implemented in a three-tier production supply chain network over a one-year period, covering the US pacific region with broad climate conditions. Numerical experiments show that transactive energy, time-of-use tariff, and climate conditions play a critical role in locating factories, warehouses, wind turbines, solar photovoltaics, and energy storage systems. Since transactive energy market brings new revenue stream, locations with stronger renewables become competitive to establish facilities despite of higher fixed and logistics cost. Contrary to the intuition, energy storage systems, which balance the intermittent power and uncertain load, have limited benefits to the cost saving.